2014
DOI: 10.3389/fnhum.2014.00034
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and attention re-orienting in autism spectrum disorders: evidence from auditory event-related potentials

Abstract: The extended phenotype of autism spectrum disorders (ASD) includes a combination of arousal regulation problems, sensory modulation difficulties, and attention re-orienting deficit. A slow and inefficient re-orienting to stimuli that appear outside of the attended sensory stream is thought to be especially detrimental for social functioning. Event-related potentials (ERPs) and magnetic fields (ERFs) may help to reveal which processing stages underlying brain response to unattended but salient sensory event are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 185 publications
(317 reference statements)
3
85
0
2
Order By: Relevance
“…Decreased P3a amplitude has been observed at younger ages (mean age 9 years) for vowel sound and speech-like frequency deviants in children with ASD and Asperger’s syndrome (Ceponiene et al, 2003; Lepisto et al, 2005, 2006). Impairment of P3a in ASD is consistent with evidence of attentional deficits in ASD (for review see Orekhova and Stroganova, 2014), and suggests a common underpinning neurobiological mechanism.…”
Section: Sensory Processing In Individuals With Asd and Fxssupporting
confidence: 53%
See 1 more Smart Citation
“…Decreased P3a amplitude has been observed at younger ages (mean age 9 years) for vowel sound and speech-like frequency deviants in children with ASD and Asperger’s syndrome (Ceponiene et al, 2003; Lepisto et al, 2005, 2006). Impairment of P3a in ASD is consistent with evidence of attentional deficits in ASD (for review see Orekhova and Stroganova, 2014), and suggests a common underpinning neurobiological mechanism.…”
Section: Sensory Processing In Individuals With Asd and Fxssupporting
confidence: 53%
“…Rather than exhaustively reviewing the literature as others have done (e.g. O’Connor, 2012; Orekhova and Stroganova, 2014), we highlight similarities and differences between auditory sensory processing deficits in ASD and FXS to highlight aspects of their shared and distinct pathophysiology. We then describe emerging evidence from rodent models which sheds light on the possible neurobiological underpinnings of sensory deficits in ASD, FXS and associated neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, unusual reactivity to sounds is noticeable early in childhood and is a powerful indicator of risk for ASD [Donkers et al, 2015;Guiraud et al, 2011;Marco, Hinkley, Hill, & Nagarajan, 2011;Orekhova et al, 2012;Osterling & Dawson, 1994]. Co-occurrence of atypical reactivity with attention deficits has leads to speculation of a causal relationship between sensory reactivity and attention, but in ASD it is unclear which stimuli are attended to, which are ignored, and how that interaction governs cognition [Allen & Courchesne, 2001;Liss, Saulnier, Fein, & Kinsbourne, 2006;Orekhova & Stroganova, 2014;Ornitz, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Early theories hypothesized that either elevated or attenuated tonic arousal was a causal factor behind some of the core ASD symptoms, such as repetitive behaviors and avoidance of social interaction (Rogers and Ozonoff 2005) Other theories have linked arousal to atypical development of face perception and other forms of social cognition. According to other influential theories, atypical regulation of arousal could cause impairments in attentional functions, an associated feature of ASD (Keehn et al 2013;Orekhova and Stroganova 2014). In addition, brain functions involved in the generation and representation of arousal have been linked to social cognition in typical development (Critchley 2005), which suggests that they may be important to disorders of social interaction such as ASD.…”
mentioning
confidence: 99%
“…A recent review suggested that atypical coupling between arousal and cortical regions involved in orienting of attention may underlie the attentional impairments in ASD (Orekhova and Stroganova 2014). Interestingly, a number of brain regions implicated in the orienting of attention were more strongly coupled to EDA in the TD compared with the ASD group.…”
mentioning
confidence: 99%